(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with recurrent pregnancy loss and recurrent implantation failure undergoing hysteroscopy at The Hanoi French Hospital from October 2023 to October 2024. Method: A prospective descriptive study including women in couples with recurrent miscarriage (before 12 weeks) of two or more episodes; women in couples with infertility who had undergone embryo transfer and were undergoing in vitro fertilization. Results: Most patients with recurrent reproductive failure were under 35 years old (79.2%), with no statistically significant difference between the recurrent pregnancy loss and repeated implantation failure groups (84.1% vs 68.8%, p = 0.078). In the recurrent pregnancy loss group, 40.6% of patients experienced four or more consecutive miscarriages. In contrast, 31.5% of patients in the repeated implantation failure group had never had a miscarriage. In the repeated implantation failure group, the mean duration of infertility was 6.13 years, and the average number of failed embryo transfers was 3.5. The rate of hysteroscopy was low in the recurrent pregnancy loss group (17.3%), whereas this rate was considerably higher in the repeated implantation failure group (50%). In the recurrent pregnancy loss group, most patients had an endometrial thickness < 7 mm (22%), while the majority of repeated implantation failure patients had an endometrial thickness within the normal range (8-14 mm). In both the recurrent pregnancy loss and repeated implantation failure groups, endometrial morphology on ultrasound was mostly irregular, characterized by scattered small hypoechoic areas or hyperechoic folds. Conclusion: The recurrent pregnancy loss and repeated implantation failure groups showed several differences in reproductive characteristics and endometrial features, but both had a high rate of irregular endometrial morphology on ultrasound. The recurrent pregnancy loss group exhibited higher rates of recurrent miscarriage and thin endometrium, whereas the repeated implantation failure group had a longer duration of infertility and more failed embryo transfers. These findings emphasize the need for thorough evaluation of the endometrium and uterine cavity in both groups, particularly the increased use of hysteroscopy to detect abnormalities related to implantation failure and recurrent pregnancy loss.